A PHARMACOLOGICAL REVIEW OF URENA LOBATA PLANT - Babu, Sayyad Sipai; Madhuri, Dasari Bindu; Ali, Shaik Liakhat (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Urena lobata, commonly known as Caesarweed or Congo jute belongs to the family Malvaceae. In India, it is widely available in Andhra Pradesh, southern and some parts of northern regions. It's leaves, roots, stem, and bark have some beneficiary activities for medicinal and non‑medicinal purposes such as antioxidant, inflammatory, antimicrobial, antidiarrheal, antidiabetic, and antihyperlipidemic, so we believe that this plant has the potential to cure many more disease and disorders than these reported activities, so this U. lobata can be a plant to be focused on for research activities. Keywords: Pharmacological activities, Antioxidant, Antimicrobial, Antidiabetic, Hypolipidemic.